Fotoperíodo e condição corporal nas respostas fisiológicas, hormonais e sanguíneas de ovelhas - Amaral, Daniele Francine (2008)
This work was carried out in the Arenito Research Center, located in Cidade Gaúcha, Nothwest of Paraná State, which belongs to the Universidade Estadual de Maringá -UEM, situated at 23°25' south latitude and 55°56' west longitude, from july of 2005 to july of 2006. With the objective of to study the photoperiod effect and feed supplementation on physiological and hormones responses of ewes, a total of 47 females ovine were used, being 16 Santa Inês breed, 16 Texel and 15 Ile de France breed. The animals were kept in aruana grass and divided in two groups, one group receiving feed supplementation of 12% of crude protein (CP) (T1), and the second receiving feed supplementation of 16% of CP (T2). There were considered air temperature, relative humidity, air velocity and black globe temperature, solar radiation and rainfall data. There were also weekly verified the rectal temperature (RT), heart rate (HR) and respiratory rate (RR) of the animals. Every month there were collected blood samples to verify triiodotyronine (T3), tyroxin (T4), glucose (Gl), total protein in blood (Ptt) and blood albumin (Alb). Even having variations on climate variables the homeothermy was kept. HF and RF can be considered a good indicator of thermal stress. T3 concentrations were affected by air temperature, showing lower concentrations at heat stress; air temperature did not affect Gl, Ptt or Alb. Ptt and Alb were higher in the T2, as was expected. Among the studied breeds Santa Inês had a standard secretion of hormones as expected, without seasonal variat.